2016
DOI: 10.1073/pnas.1600582113
|View full text |Cite
|
Sign up to set email alerts
|

Versatile in vivo regulation of tumor phenotypes by dCas9-mediated transcriptional perturbation

Abstract: Targeted transcriptional regulation is a powerful tool to study genetic mediators of cellular behavior. Here, we show that catalytically dead Cas9 (dCas9) targeted to genomic regions upstream or downstream of the transcription start site allows for specific and sustainable geneexpression level alterations in tumor cells in vitro and in syngeneic immune-competent mouse models. We used this approach for a highcoverage pooled gene-activation screen in vivo and discovered previously unidentified modulators of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 59 publications
0
76
0
Order By: Relevance
“…1A). After the initial proof-of-concept experiment (Cheng et al, 2013; Farzadfard et al, 2013; Gilbert et al, 2013; Maeder et al, 2013; Mali et al, 2013a; Perez-Pinera et al, 2013; Qi et al, 2013), numerous studies have validated this approach and further refined the experimental systems utilized (Perez-Pinera et al, 2013; Chakraborty et al, 2014; Gilbert et al, 2014; Kearns et al, 2014; Balboa et al, 2015; Kearns et al, 2015; Konermann et al, 2015; Nihongaki et al, 2015; Polstein and Gersbach, 2015; Shechner et al, 2015; Thakore et al, 2015; Zalatan et al, 2015; Black et al, 2016; Braun et al, 2016; Chavez et al, 2016; Gao et al, 2016; Garcia-Bloj et al, 2016; Genga et al, 2016; Himeda et al, 2016; Mandegar et al, 2016; Pradeepa et al, 2016; Radzisheuskaya et al, 2016; Klann et al, 2017). …”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). After the initial proof-of-concept experiment (Cheng et al, 2013; Farzadfard et al, 2013; Gilbert et al, 2013; Maeder et al, 2013; Mali et al, 2013a; Perez-Pinera et al, 2013; Qi et al, 2013), numerous studies have validated this approach and further refined the experimental systems utilized (Perez-Pinera et al, 2013; Chakraborty et al, 2014; Gilbert et al, 2014; Kearns et al, 2014; Balboa et al, 2015; Kearns et al, 2015; Konermann et al, 2015; Nihongaki et al, 2015; Polstein and Gersbach, 2015; Shechner et al, 2015; Thakore et al, 2015; Zalatan et al, 2015; Black et al, 2016; Braun et al, 2016; Chavez et al, 2016; Gao et al, 2016; Garcia-Bloj et al, 2016; Genga et al, 2016; Himeda et al, 2016; Mandegar et al, 2016; Pradeepa et al, 2016; Radzisheuskaya et al, 2016; Klann et al, 2017). …”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…These strategies can be a useful alternative to transgene overexpression or antisense-mediated gene repression. In fact, several studies have already demonstrated its applicability in the validation of gene functionality (Gilbert et al, 2014; Chavez et al, 2016; Radzisheuskaya et al, 2016), interrogation of promoter and enhancer regions (Kearns et al, 2015; Zalatan et al, 2015; Himeda et al, 2016; Klann et al, 2017), induction of direct cell fate conversion (Chakraborty et al, 2014; Balboa et al, 2015; Black et al, 2016), reprogramming to pluripotency (Balboa et al, 2015; Xiong et al, 2016), genome-scale transcriptional modifications (Gilbert et al, 2014; Konermann et al, 2015) and proof of concept therapeutic approaches against various diseases (Bialek et al, 2016; Braun et al, 2016; Garcia-Bloj et al, 2016). …”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…Although multiple sgRNAs tiling the proximal promoter of the target gene can synergistically boost the dCas9-VP64-mediated gene activation 79,1215 , this strategy reduces the scalability of the system 2 and may increase the risk of dCas9-mediated transcriptional perturbation at off-target non-promoter loci 1517 . Therefore, we sought to devise and screen for an improved dCas9-TAD (Fig.…”
mentioning
confidence: 99%
“…We envision that dCas9-TV will be particularly useful in basic and applied plant research, including but not limited to: (i) when combined with a genome-scale sgRNA library, dCas9-TV can be used in protoplast-based gain-of-function screens for regulatory genes in a signaling pathway of interest using a promoter-LUC/GFP reporter as a signaling readout; (ii) it is useful for generating a synthetic plant transcriptome 25 to study the functions of transcription regulators; (iii) it can be applied in metabolic engineering by multiplex activation of lowly expressed enzymes throughout a metabolic pathway to increase the production of valuable metabolites; (iv) it can also be applied to upregulate crop genes conferring beneficial traits such as biotic and abiotic resistances. Future efforts will be needed to improve the rational design of sgRNAs, as different sgRNAs targeting the same promoter can lead to variable transcriptional regulation by the same dCas9 activators 2,7,9,1217 (Supplementary Figs. 2, 5 and 11), and a straightforward correlation between the parameters of sgRNAs (e.g., GC content or target site location, Supplementary Table 2) and their gene activation efficiencies has not been established.…”
mentioning
confidence: 99%
“…In vivo cancer induction using ATFs was demonstrated by Hemann and colleagues, by regulating the transcription of cancer-related genes such as Trp53 and Mgmt using dCas9 and dCas9-VP64 [57]. Trp53 gene was silenced by dCas9/sgRNA designed to target downstream of transcription start site in lymphoma cells, and then the cells were transplanted into recipient mice.…”
Section: Expanded Applications Using the Synthetic Atf Systemsmentioning
confidence: 99%